Design and fabrication of foldable magazine rack - Mohd Harris, Abdul Aziz (2008)
This thesis is based on the project of designing and fabricating a foldable magazine rack. The 'Foldable Magazine Rack' is a product that is used for storing magazines and newspapers in a tidy manner. The fabrication of this product started with surveying in the market about the product, specification analysis, concept designing, detailed concept designing and fabrication of the product. Four (4) products were selected from the market for the analysis and investigation. One of the products that is suitable and fits all the specification was chosen to fabricate. The investigation was made in scope of the constraints that may occur for the development of the product and the relevance of the product manufacturing processes. This product has been fabricated according to basic manufacturing methods through many fabrication processes such as cutting, drilling, bending, and assembling. For the development of this project in future works, some suggestion was made for upgrading the product. The suggestions are designing a larger base to make it more stable and use a more durable material to make sure this product will be competitive with the existing products in the market.